A case study on the role of security elements as deterrents to shoplifting incidents in a grocery store in Metro Manila based on its interior design - Castor, Eunice Mae DS.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The purpose of this case study is to assess the existing security elements of a selected grocery store in Metro Manila based on the Crime Prevention Through Environmental Design (CPTED) model developed by Newman (1972) and relate these elements to the documented shoplifting incidents in the year 2015 within the grocery store.The CPTED model of Newman (1972) that was used as a framework includes four main dimensions of crime prevention, namely: access control, surveillance, maintenance, and territoriality. This model was utilized to point out the strengths and weaknesses of the existing security elements in relation to shoplifting as a crime, but did not aim to provide direct solutions to the space. The qualitative mixed-methods research design utilized site observation and face-to-face interviews with purposively chosen respondents. A total of fourteen (14) administrative staff and employees were interviewed and an observation checklist adapted from the CPTED model was used to gather factual data about the security elements of the interior. The findings of the study showed that the following security elements were present in the interior: physical barriers, signage, lighting, parallel layout of shelves to cashier counters, Closed Circuit Televisions (CCTVs), and aesthetic branding. Additionally, human intervention, such as security and employee patrol, also emerged as security functions of the store. The presence of the security elements in the interiors, with the CPTED model as the basis, was assessed as strengths. The built interior may have a positive effect on the recorded shoplifting incidents. However, the data revealed that the existing security elements in the interior do not entirely deter shoplifting due to some lapses in the security. Thus, it is recommended that other factors and theories should be considered in having a deeper understanding of security elements in the interior as deterrents to shoplifting.
Thesis (BS Interior Design)--University of he Philippines Diliman.
Keywords: Grocery trade -- Security